Integration of Local Potential from Grenden Village into Science E-Modules to Enhance the Science Process Skills of Junior High School Students (Universitas Pendidikan Indonesia, 2026)
Understanding the scientific process plays an important role in junior high school science education. These skills include observing, categorizing, hypothesizing, analyzing data, and communicating findings. However, various studies show that junior high school students in Indonesia still struggle to develop these skills effectively. One of the leading causes of this problem is the lack of contextual relevance in teaching materials that do not focus on improving science process skills. Therefore, this research aims to improve students' understanding of the basic concepts of thermodynamics, especially temperature and heat, by developing e-modules integrated with the local context in Grenden Village, Jember. The ADDIE model developed the e-module, which includes five systematic phases, analysis, design, development, implementation, and evaluation. Data were collected through validation sheets, practicality questionnaires, pretest and posttest instruments, and student response questionnaires. The N-gain value of 0.68 indicated a moderate level of improvement, demonstrating that the e-module effectively enhanced students’ science process skills. The student response questionnaire yielded an average score of 78.95% (good). Overall, the e-module based on the local potential of Grenden Village is valid, practical, and effective, making it suitable for use in junior high school science learning and as a foundation for further research.